CLIMATE CHANGE MITIGATION ON INVESTOR REACTION: THROUGH FINANCIAL PERFORMANCE DIGITAL TRANSFORMATION AND BANK PERFORMANCE - Siti Nurul Fathimah; Nofryanti; Iin Rosini (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to examine climate change mitigation Carbon Emissions Disclosure and Green Investment on Investor Reaction through Financial Performance. This research is classified as associative quantitative research. The type of data used is secondary data obtained from www.idx.co.id and the company's website. The population in this study were non-financial sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. While the sample of this study was determined by purposive sampling method so that 41 sample companies were obtained. The analysis method used is Panel data Model Regression analysis and testing the mediation hypothesis is done by using the Sobel test. The results of this study indicate that Carbon Emissions Disclosure has a significant effect on Investor Reaction, Green Investment has no effect on Investor Reaction, Financial Performance has a significant effect on Investor Reaction, Carbon Emissions Disclosure has no effect on Financial Performance, Green Investment has a significant effect on Financial Performance, Financial Performance is unable to mediate the effect of Carbon Emissions Disclosure on Investor Reaction, and Financial Performance is able to mediate the effect of Green Investment on Investor Reaction.